Did Strategic Bombing in the Second World War Lead to 'German Angst'? A Large–Scale Empirical Test across 89 German Cities. Issue 3 (May 2017) - Obschonka, Martin; Stuetzer, Michael; Rentfrow, P. Jason; Potter, Jeff; Gosling, Samuel D.
A widespread stereotype holds that the Germans are notorious worriers, an idea captured by the term German angst . An analysis of country–level neurotic personality traits (trait anxiety, trait depression, and trait neuroticism; N = 7 210 276) across 109 countries provided mixed support for this idea; Germany ranked 20th, 31st, and 53rd for depression, anxiety, and neuroticism, respectively, suggesting, at best, the national stereotype is only partly valid. Theories put forward to explain the stereotypical characterization of Germany focus on the collective traumatic events experienced by Germany during World War II (WWII), such as the massive strategic bombing of German cities. We thus examined the link between strategic bombing of 89 German cities and today's regional levels in neurotic traits ( N = 33 534) and related mental health problems. Contrary to the WWII bombing hypothesis, we found negative effects of strategic bombing on regional trait depression and mental health problems. This finding was robust when controlling for a host of economic factors and social structure. We also found Resilience × Stressor interactions: Cities with more severe bombings show more resilience today (lower levels of neurotic traits and mental health problems in the face of a current major stressor—economic hardship). Copyright © 2017 European Association of Personality Psychology